SCREEN TIME AND SPEECH DELAY: ANALYZING THE DANGERS OF USING GADGETS ON LANGUAGE DEVELOPMENT IN CHILDREN AGED 1-3 YEARS - Harahap, Raysha Zahra; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
Gadget is a small electronic device that has many special functions. In addition, gadgets can also be interpreted as modern devices that have a number of applications in them. These applications are used as sources of information, social networks, hobbies, creativity, and various other uses. The purpose of this study is to know how dangers of using gadgets on language production in children aged 1-3 years. In this digital era, most parents allow their children to use gadgets. The goal is to provide entertainment or just entertainment to relieve children's boredom. In addition, gadgets are also often used so that children can sit still without whining for various things. That way, parents can freely do various pending jobs. Using gadgets at an early age of less than two years can increase the risk of children experiencing delays in their development, including speech delays. This study is a qualitative descriptive analysis research. This descriptive research aims to describe a situation or phenomena as it is. Data collection techniques used in the study were library research. The result of this study is to ascertain three things (1) language development in early childhood (2) The dangers of giving excessive gadgets to young children between the ages of 1-3 years.